Perlindungаn Hukum bаgi Debitur Penerimа Kredit Usаhа Rаkyаt yаng Wаnprestаsi Kаrenа Overmаcht pаdа Perjаnjiаn Kredit Bаnk - Nova, Maria; Suhariningsih, Suhariningsih; Sugiri, Bambang (Universitas Negeri Malang, 2020)
The purpose of this study was to examine the forms of special treatment for debtors who were receiving business loans as victims of natural disasters that occurred in Palu City, Central Sulawesi Province, and legal protection for debtors who were receiving business loans. This study used empirical legal methods. The results of the study indicated that the form of special treatment for debtors receiving business loans as victims of natural disasters referred to the Financial Services Authority Regulation Number 45/POJK.03/2017 concerning Special Treatment of Credit or Bank Financing for Certain Areas in Indonesia Affected by Natural Disasters. Legal protection provided if the credit restructuring provided in the form of a delay in payment of obligations (grace period) had not been optimal could be in the form of an extension of credit restructuring, new treaty addendum, or write off.